What Is Religious Education for? Exploring SACRE Member Views. Issue 1 (2nd January 2020) - Plater, Mark
Abstract: In recent years, concern has been expressed about lack of clarity in the published aims and purposes provided for the teaching of religious education (RE) in English schools. Public reports and significant RE authorities suggest that this contributes to teacher confusion and a lowering of standards in the subject. As a contribution to the debate, 513 Standing Advisory Council for RE (SACRE) members offer their responses to an online survey about competing alternative aims for the subject. The results provide fascinating data on the perspectives of one of RE's key stakeholder groups.